2009
DOI: 10.1108/17511060911004888
|View full text |Cite
|
Sign up to set email alerts
|

Pride and prejudice in the evaluation of wine?

Abstract: PurposeThe region where a wine is produced is a factor that influences consumers' preferences and price perceptions. For most consumers, a wine from an established place like France would be preferred over a wine from less established place, like Texas. However, a consumer's identity with their home area (not well known for wine) may override such an effect. Thus, the purpose of this paper is to determine whether a wine's geographic origin influences wine preference and price perceptions and, if so, whether id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 24 publications
1
28
1
1
Order By: Relevance
“…While previous research has demonstrated that wine from an Old World wine country is perceived more favorably than wine from a New World wine country (Guidry et al, 2009), research has not explored why that could be the case. This research suggests that one reason is the wine's perceived authenticity; that is, perceived authenticity mediates the effect of country of origin on one's WTP for the wine.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…While previous research has demonstrated that wine from an Old World wine country is perceived more favorably than wine from a New World wine country (Guidry et al, 2009), research has not explored why that could be the case. This research suggests that one reason is the wine's perceived authenticity; that is, perceived authenticity mediates the effect of country of origin on one's WTP for the wine.…”
Section: Discussionmentioning
confidence: 98%
“…In one study, participants tasted both a supposed French (Old World) wine and a supposed Texas (New World) wine, although the two wines were actually identical (Guidry et al, 2009). The results showed that the supposed French wine was perceived to be of higher quality than the supposed Texas wine.…”
Section: Origin Effects and Product Ethnicity: The Case Of Old World mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this time we tested reactions to champagne. Unlike other studies, in which all participants tasted the same product in all experimental conditions (Guidry et al, 2009), we used two different brands available on the market. In the national brand condition, we used a brand owned by one of the world's leading wine and spirits groups.…”
Section: Design Stimuli and Participantsmentioning
confidence: 99%
“…Maheswaran und Chen 2006). So verbinden einige Käufer mit dem Erwerb von Produkten bestimmter Herkunft Stolz, Prestige oder Sympathie (Batra et al 2000;Guidry et al 2009;Zhongqi et al 2006). Die einem Land entgegengebrachte Antipathie und die dadurch ausgelöste Ablehnung der dort hergestellten Produkte erforschten erstmals Klein et al (1998) (Baker und Ballington 2002, S. 160).…”
Section: Affektive Prozesseunclassified